Aproximación a la distribución de los costos directos de la diabetes tipo 2 en Colombia - Eduar D Echeverri; Alvaro J Ruiz-Morales; Martin Rondon; Diego Rosselli (Instituto Nacional de Salud Pública, 2022)
No disponible